Enhanced Genotoxicity of Silver Nanoparticles in DNA Repair Deficient Mammalian Cells - Lim, Hui Kheng; AshaRani, P. V.; Hande, M. Prakash (Frontiers in Genetics, 2012)
Silver nanoparticles (Ag-np) have been used extensively in medicine and commercially due to their anti-microbial properties. Therapeutic potentials of these nanoparticles are being explored extensively despite the lack of information on their mechanism of action at molecular and cellular level. Here, we have investigated the DNA damage response and repair following Ag-np treatment in mammalian cells. Studies have shown that Ag-np exerts genotoxicity through double strand breaks (DSBs). DNA-PKcs, the catalytic subunit of DNA dependent protein kinase, is an important caretaker of the genome which is known to be the main player mediating non-homologous end joining (NHEJ) repair pathway. We hypothesise that DNA-PKcs is responsible for the repair of Ag-np induced DNA damage. In vitro studies have been carried out to investigate both cytotoxicity and genotoxicity induced by Ag-np in normal human cells, DNA-PKcs proficient and deficient mammalian cells. Chemical inhibition of DNA-PKcs activity with NU7026, an ATP-competitive inhibitor of DNA-PKcs, has been performed to further validate the role of DNA-PKcs in this model. Our results suggest that Ag-np induced more prominent dose-dependent decrease in cell viability in DNA-PKcs deficient or inhibited cells. The deficiency or inhibition of DNA-PKcs renders the cells with higher susceptibility to DNA damage and genome instability. DSBs induction and DNA-PKcs activation were subsequently observed and contributed to greater cell cycle arrest/cell death. These findings support the fact that DNA-PKcs is involved in the repair of Ag-np induced genotoxicity and NHEJ repair pathway in particular DNA-PKcs as defence mechanism is activated to safeguard the genome upon Ag-np exposure.